Maritime spatial planning. Past, present, future. - (:unkn) unknown (Palgrave Macmillan, 2019)
The book is the first comprehensive overview of maritime or marine spatial planning. Countries across the globe are beginning to implement maritime spatial plans; however the authors of the collection have identified several key questions that are emerging from the growing body of MSP experience. How can maritime spatial planning deal with a complex and dynamic environment such as the sea? How can MSP be embedded in multiple levels of governance across regional and national borders - and how far does the environment benefit from this new approach? The book actively engages with the problems encapsulated in these questions, and explores possible solutions. Situated at the intersection between theory and practice, the volume draws together several strands of interdisciplinary research, reflecting on the history of MSP as well as examining current practice and looking towards the future. The authors and contributors examine MSP from disciplines as diverse as geography, urban planning, political science, natural science, sociology and education; reflecting the growing critical engagement with MSP in many academic fields.
Keywords: Raumplanung; Raumentwicklung; Meer; Theorie; Praxis; Küste; Ökosystem; Naturschutz; Standorttheorie; Soziokultur; Nachhaltigkeit; Umweltverträglichkeit; Macht; Partizipation; Küstenschutz; Seerecht; Internationales Recht; Internationale Zusammenarbeit; Meerespolitik; Meeresnutzung; Soziale Nachhaltigkeit